Multicultural and Social Justice Competence in Clinical Supervision. (1st December 2019) - Fickling, Melissa J.; Tangen, Jodi L.; Graden, Matthew W.; Grays, Darita
Abstract : The authors apply the Multicultural and Social Justice Counseling Competencies (Ratts, Singh, Nassar‐McMillan, Butler, & McCullough, 2015) model to clinical supervision, highlighting ways for supervisors to intentionally integrate multicultural and social justice practices into the supervision enterprise. They offer specific implications for supervision practice, including a focus on broaching strategies.